Neuroprotective effect of riboflavin kinase on cerebral ischemia injury in rats - Yingxin Zou; Minghua Ruan; Xu Feng; Fei Liu; Weihong Liu; Song Chen; Zhiyong Chu (Molecular Medicine)
Abstract Background Riboflavin kinase (RFK, also called flavokinase) is a catalytic enzyme that converts riboflavin to its active form in vivo. Dysfunction of the RFK gene has been associated with susceptibility to ischemic stroke. However, the protective role and mechanisms of RFK in ischemic stroke have not been elucidated. Methods Lentivirus-mediated RFK knock-up (RFK( +)) and knock-down (RFK(-)) were used to investigate the protective effect and mechanism of RFK in the rat middle cerebral artery occlusion (MCAO) model in vivo and in the oxygen and glucose deprivation (OGD) model of neurons in vitro; and the dependence of the protective effect of RFK on flavins was also investigated. Results We demonstrated that RFK was an endogenous protein against ischemia brain injury both in vivo and in vitro experiments. RFK inhibited cerebral infarction, cerebral edema and neuronal apoptosis after cerebral ischemia. Its mechanisms include inhibition of the protein expression of Caspase 12 and Caspase 3 induced by cerebral ischemia, and thus inhibiting endoplasmic reticulum stress (ERS) and neuronal apoptosis; the protective effect of RFK depends on the presence of the flavoprotein Ero1; exogenous riboflavin supplementation protected cortical neurons from ischemic injury and prolonged the lifespan in stroke-prone spontaneously hypertensive rats with low RFK gene function, but this protective effect is limited and cannot completely reverse the decreasing trend of neuronal tolerance to ischemic injury caused by RFK gene dysfunction; the protective effect of RFK against ischemic injury is independent of the presence of flavins and their concentrations. Conclusions The present study demonstrates that RFK is an important regulatory molecule against ischemia brain injury and its mechanism involves inhibition of ERS. The protective effect of RFK is independent of the presence of flavins and their concentrations. RFK deserves further investigation as a promising target gene for the detection of stroke susceptibility. Flavins may be used as a preventive or adjunctive treatments for ischemic brain injury. Graphical Abstract